Figure 6 from: Cripps CL, Eberhardt U, Schütz N, Beker HJ, Evenson VS, Horak E (2019) The genus Hebeloma in the Rocky Mountain Alpine Zone. MycoKeys 46: 1-54. https://doi.org/10.3897/mycokeys.46.32823 - Cripps, Cathy L.; Eberhardt, Ursula; Schütz, Nicole; Beker, Henry J.; Evenson, Vera S.; Horak, Egon (Zenodo, 2019)
Figure 6 ML results and pruned quasi-median networks of species complexes of Hebelomasect.Hebeloma.AH.nigellum complex BH.mesophaeum complex. In ML trees, branches supported by ≥ 80% bootstrap (1000 replicates) are double width. In networks, the size of the circles corresponds to the number of sequences they represent. Circles shared by two or more taxa are divided according to the number of representatives for each species. FE and RM refer to the origin of the collections, Europe or Rocky Mountains, respectively. Placement of type sequences is indicated as follows: A * = H.clavulipes. ** = H.oreophilum, † = H.spetsbergense, ‡ = H.nigellum (not included in the network analysis), § = H.hygrophilum; B * = H.pubescens, ** = H.excedens, † = H.subargillaceum, ‡ = H.nigromaculatum, § = H.littenii, ¶ = H.alpinicola, # = H.perigoense, †† = H.chapmaniae and ‡‡ = H.smithii.